2017
DOI: 10.1186/s12886-017-0427-1
|View full text |Cite
|
Sign up to set email alerts
|

Reverse pupillary block after implantation of a scleral-sutured posterior chamber intraocular lens: a retrospective, open study

Abstract: BackgroundTo report the clinical features of patients with reverse pupillary block (RPB) after scleral-sutured posterior chamber intraocular lens (PC IOL) implantation and biometric changes after laser peripheral iridotomy (LPI).MethodsEight patients attending our hospital’s ophthalmology outpatient clinic, who developed RPB after implantation of a scleral-sutured PC IOL due to subluxation of the crystalline lens or IOL, were investigated in this retrospective, observational study.ResultsPreoperative evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…In a 2018 study, Stem et al [ 3 ] reported the rate of increased IOP as 23%, which they attributed to RPB developing postoperatively, and recommended performing intraoperative prophylactic iridotomy in these patients. RPB is a rare finding after the scleral fixation of IOL, but it may result in pigment dispersion or iris capture and therefore might require treatment with postoperative laser peripheral iridotomy to prevent these negative effects [ 11 , 12 ]. In our study, RPB was not observed in any of the patients as a result of intraoperative prophylactic iridotomy being performed in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2018 study, Stem et al [ 3 ] reported the rate of increased IOP as 23%, which they attributed to RPB developing postoperatively, and recommended performing intraoperative prophylactic iridotomy in these patients. RPB is a rare finding after the scleral fixation of IOL, but it may result in pigment dispersion or iris capture and therefore might require treatment with postoperative laser peripheral iridotomy to prevent these negative effects [ 11 , 12 ]. In our study, RPB was not observed in any of the patients as a result of intraoperative prophylactic iridotomy being performed in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…It seems closely related to a history of trauma in view of existence of cyclodialysis and iridodonesis [ 10 ]. Iridodonesis is a risk factor for pupillary capture after suturing and intrascleral fixation of an IOL [ 11 ]. Repairing cyclodialysis is often technically difficult due to softness and flexibility of the iris and the narrow space between the cornea and lens.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…After the surgery, the removal of the lens capsule and the lens zonular fibers with vitreous preserved a greater posterior chamber volume resulted in iris backward and more aqueous humor flowing into the anterior chamber [ 43 , 44 ] to push IOL up. And iris depigmentation due to the contact between IOL and the iris pigment epithelium might cause angle pigmentation, which slowed the aqueous humor flowing out from the anterior chamber [ 45 ]. We speculated these four reasons are responsible for pupillary capture.…”
Section: Discussionmentioning
confidence: 99%